The assessment and management of dementia - Zahir Vally (South African Family Practice)
South African family practitioners can expect to contend with rising rates of dementia as the aged segment of the population grows larger and HIV-related neuropsychiatric complications manifest with increasing prevalence. Family practitioners are often the first professional consulted by families concerned with a family member’s suspected dementia. This fortunate position facilitates the early identification of cognitive difficulties, which, in turn, greatly increases the likelihood of optimal management. Dementia is best managed with a multidisciplinary-team approach that sees family practitioners fulfilling the role of key support to families and of the coordinators of multidisciplinary referrals and inputs. This article reviews the key diagnostic features of dementia and provides suggestions that may be utilised by physicians in the basic assessment of these features. It concludes with a summary of the most appropriate management plan to be adopted by family practitioners.